Colour in Robert W. Chambers' The King in Yellow - Brož, Antonín (Univerzita Pardubice, 2021)
The thesis deals with a collection of short stories The King in Yellow (1895) by the American writer Robert W. Chambers (1865-1933). It primarily focuses on the role of yellow as a meaning-making and symbolic component of the narrative. The theoretical part concerns the aesthetic perception of yellow and its popularity during the fin de siecle period, i.e. in the context of Symbolism, Aestheticism, decadence, degeneration and the feeling of decline or perversion. The practical part concentrates fully on the selected work The King in Yellow. It examines the motif of yellow, present in the character of The King in Yellow and Yellow Signs, against the background of the theoretical part and verifies the degree of participation of other authors in the turn-of-the-century trend to thematize this colour in their literary works.
Barva v díle The King in Yellow Roberta W. Chamberse
Keywords: žlutá barva; Chambers, Robert W.; Král ve žlutém; barvy; symboly; dekadence; fin de siecle; yellow colour; Chambers, Robert W.; The King in Yellow; colours; symbols; decadence; fin de siecle